Heterogeneity in testing practices for infections during pregnancy: national survey across Switzerland (Swiss Medical Weekly, 2016)
QUESTION: Detection and treatment of infections during pregnancy are important for both maternal and child health. The objective of this study was to describe testing practices and adherence to current national guidelines in Switzerland. METHODS: We invited all registered practicing obstetricians and gynaecologists in Switzerland to complete an anonymous web-based questionnaire about strategies for testing for 14 infections during pregnancy. We conducted a descriptive analysis according to demographic characteristics. RESULTS: Of 1138 invited clinicians, 537 (47.2%) responded and 520 (45.6%) were eligible as they are currently caring for pregnant women. Nearly all eligible respondents tested all pregnant women for group B streptococcus (98.0%), hepatitis B virus (HBV) (96.5%) and human immunodeficiency virus (HIV) (94.7%), in accordance with national guidelines. Although testing for toxoplasmosis is not recommended, 24.1% of respondents tested all women and 32.9% tested at the request of the patient. Hospital doctors were more likely not to test for toxoplasmosis than doctors working in private practice (odds ratio [OR] 2.52, 95% confidence interval [CI] 1.04–6.13, p = 0.04). Only 80.4% of respondents tested all women for syphilis. There were regional differences in testing for some infections. The proportion of clinicians testing all women for HIV, HBV and syphilis was lower in Eastern Switzerland and the Zurich region (69.4% and 61.2%, respectively) than in other regions (range 77.1–88.1%, p